Dissecting the Crosstalk Between Nrf2 and NF-κB Response Pathways in Drug-Induced Toxicity - Gao, Wen; Guo, Lin; Yang, Yan; Wang, Yu; Xia, Shuang; Gong, Hui; Zhang, Bi-Kui; Yan, Miao (Frontiers in Cell and Developmental Biology, 2022)
Nrf2 and NF-κB are important regulators of the response to oxidative stress and inflammation in the body. Previous pharmacological and genetic studies have confirmed crosstalk between the two. The deficiency of Nrf2 elevates the expression of NF-κB, leading to increased production of inflammatory factors, while NF-κB can affect the expression of downstream target genes by regulating the transcription and activity of Nrf2. At the same time, many therapeutic drug-induced organ toxicities, including hepatotoxicity, nephrotoxicity, cardiotoxicity, pulmonary toxicity, dermal toxicity, and neurotoxicity, have received increasing attention from researchers in clinical practice. Drug-induced organ injury can destroy body function, reduce the patients’ quality of life, and even threaten the lives of patients. Therefore, it is urgent to find protective drugs to ameliorate drug-induced injury. There is substantial evidence that protective medications can alleviate drug-induced organ toxicity by modulating both Nrf2 and NF-κB signaling pathways. Thus, it has become increasingly important to explore the crosstalk mechanism between Nrf2 and NF-κB in drug-induced toxicity. In this review, we summarize the potential molecular mechanisms of Nrf2 and NF-κB pathways and the important effects on adverse effects including toxic reactions and look forward to finding protective drugs that can target the crosstalk between the two.